LAPORAN KEUANGAN PEMERINTAH DAERAH: Mengerek Responsi dan Partisipasi Masyarakat Sebagai Suatu Keniscayaan - Adi, Agustinus Santoso (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2011)
During this time responsiveness and participation in local financial management processes -including financial statements - is still relatively low. Community participation should be given atevery stage of financial management areas ranging from drafting and ratification of the budget,implementation, up to local financial accountability reports. Constraints in the development ofresponsiveness and participation in local finance partly because of the lack of socialization intothe community and the difficulty of accessing a variety of public policy. The lack of responsivenessis also due to the lack of government support in the form of laws and regulations such as localregulations (Regulation). This article tried to give a review of the concept: good governmentgovernance, public accountability, accounting and operational scope of local government andthe local government financial statements. In this article also discussed advocacy and effortsto develop indicators of financial statements responsive community. Discussion of advocacyand the development of indicators in an attempt to overcome the lack of responsiveness andparticipation. An understanding of the concepts, advocacy and the development of indicatorsof financial statements responsive community are expected to be the starting point to promotethe establishment of good governance and accountability local goverment in governancecorrespondence with community participation